Gels for Removal and Adsorption (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue is focused on the application of gels for adsorption and removal. The targeted substances include, but are not limited to, gaseous, liquid, and solid states. The gaseous matters can be poisonous gases, greenhouse gases, etc. The liquid matters include wastewaters containing oils, heavy metal ions, radioactive materials, dyes, and antibiotics. This Special Issue shows research on the adsorption and removal of other special states of matter, such as plasmas, supercritical materials, liquid crystals, and superconductive materials. More importantly, the adsorption and removal mechanisms of gels, especially structure–activity relationships, should also be highlighted. This Special Issue also covers gels for the absorption and controlled release of drugs in postoperative repair dressing and wound healing. For these applications, the gels have to be constructed responsively or intelligently geared towards certain environmental stimulation, such as pH, light, magnetic field, electric field, and temperature for controlled drug release. The publication of original research articles, rapid communications, and reviews in this Special Issue will make an important contribution to developing gels for removal and adsorption.